2004
DOI: 10.1128/jvi.78.13.7131-7137.2004
|View full text |Cite
|
Sign up to set email alerts
|

Selection Pressure-Driven Evolution of the Epstein-Barr Virus-Encoded Oncogene LMP1 in Virus Isolates from Southeast Asia

Abstract: The geographically constrained distribution of Epstein-Barr virus (EBV)-associated nasopharyngeal carcinoma (NPC) in southeast Asian populations suggests that both viral and host genetics may influence disease risk. Although susceptibility loci have been mapped within the human genome, the role of viral genetics in the focal distribution of NPC remains an enigma. Here we report a molecular phylogenetic analysis of an NPC-associated viral oncogene, LMP1, in a large panel of EBV isolates from southeast Asia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
(22 reference statements)
2
32
0
1
Order By: Relevance
“…The five LMP1 strains identified in the Thai population were also found in patients with lymphoma in Malaysia (Kim & Peh, 2003), with NPC in Thailand (Tiwawech et al, 2008), Indonesia (Burrows et al, 2004) and Vietnam (Nguyen- Van et al, 2008) and with T-cell diseases in Thailand (Saechan et al, 2006). The LMP1 strains found in this study have also been identified in other geographical areas (Edwards et al, 1999;Saechan et al, 2006;SitkiGreen et al, 2002SitkiGreen et al, , 2003, where the majority and distribution patterns of strains reflect geographical location.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The five LMP1 strains identified in the Thai population were also found in patients with lymphoma in Malaysia (Kim & Peh, 2003), with NPC in Thailand (Tiwawech et al, 2008), Indonesia (Burrows et al, 2004) and Vietnam (Nguyen- Van et al, 2008) and with T-cell diseases in Thailand (Saechan et al, 2006). The LMP1 strains found in this study have also been identified in other geographical areas (Edwards et al, 1999;Saechan et al, 2006;SitkiGreen et al, 2002SitkiGreen et al, , 2003, where the majority and distribution patterns of strains reflect geographical location.…”
Section: Discussionsupporting
confidence: 54%
“…Although this protein is essential for the oncogenic potential of EBV, little is known about sequence variation in the LMP1 gene of EBV isolates among the general population in South-east Asia. Only limited LMP1 sequences that have been isolated from patients with nasopharyngeal carcinoma (NPC) in Thailand, Indonesia and Vietnam and with lymphomas in Malaysia and Thailand have been reported (Burrows et al, 2004;Kim & Peh, 2003 (Burrows et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1). It is thought that LMP1 evades host immunity by having multiple variations as a result of positive selection [37]. These results suggest that EBV can evolve under the exposure to host immunity and survive in various substrains.…”
Section: Discussionmentioning
confidence: 89%
“…The sequence variations of vIL-10 were much smaller than those of LMP1, suggesting a weaker positive selection pressure for the IL-10 versus the LMP1 molecules [37,38]. vIL-10 functions as a cytokine, similar to hIL-10 [14,15,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Many epitopes for CTL surveillance have been mapped in EBV antigens and correlated with MHC type. There is some clear evidence for epitope selection based on immune surveillance (Burrows et al 2004;Midgley et al 2003a, b;Nagamine et al 2007;Tang et al 2008;Lin et al 2004Lin et al , 2005Duraiswamy et al 2003). Evidence for positive selection also comes from ratios of non-synonymous to synonymous changes in the SNPs present in reading frames (Palser et al 2015).…”
Section: Broad Aspects Of Genome Variation-ebv Types Selection Forcementioning
confidence: 96%